Development Of Community-Based Halal Tourism In The Indonesia-Malaysia Border Region - Oggy Akmadani (CV Putra Publisher, 2026)
This article examines the development of community-based halal tourism in Temajuk Village, Paloh District, Sambas Regency, as an Indonesia-Malaysia border destination. The study is relevant because Temajuk possesses strong natural, cultural, and Islamic identity assets, whilst still facing limitations in accessibility, amenities, communication networks, destination governance, and tourism regulation. This study employs a descriptive qualitative approach, which includes in-depth interviews, observation, focus group discussions, and source triangulation. The findings show that local communities play a central role in shaping halal tourism experiences through social hospitality, the cultural practice of jerampah, homestay management, local products, tourism awareness groups, festivals, and social media promotion. However, community initiatives remain limited when they are not supported by a master plan, halal service standards, visitor data, banking access, electricity, internet, and multi-stakeholder partnerships. This article proposes the Border Community Five-Capital Model, comprising natural-cultural capital, social capital, symbolic capital, economic capital, and institutional-digital capital. The model can serve as a practical framework for strengthening the competitiveness of halal tourism destinations that are inclusive, sustainable, and oriented towards local community welfare.